The T-Shape dilemma in industrial engineering and management curriculum - Sigal Koral Kordova; Moti Frank (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: This paper deals with the undergraduate "Industrial Engineering and Management" curriculum. The research's purpose was to examine the in-depth coverage of teaching/learning in the combined field of industrial engineering and management, as opposed to the extent of widthwise multidisciplinary teaching/learning in this field (T-Shape dilemma). According to this purpose, the following research question was derived: With respect to widthwise multidisciplinary teaching and the depth extent of teaching in industrial engineering and management, what is the desired situation as opposed to the actual situation? Design/methodology/approach: In order to examine the T-shape dilemma, 16 in-depth interviews were conducted with senior-level managers in industry, and with leading academics in the fields of industrial engineering and management. The interviewees were asked questions regarding the planning and design of the curriculum in these fields. An analysis of the interviews was carried out by dividing the interviews into categories, and presenting the categories with the highest frequency occurring in all of the interviews. Findings and Originality/value: One of the most significant results was the great variability between the answers of senior-level managers in industry and those of the academics. While individuals in the business field (senior-level managers) place great importance on focusing studies on the management-business aspect, and acquiring multidisciplinary knowledge, academics emphasized the great importance of understanding the theories and rationale behind the learned material, acquiring a strong theoretical basis, and studying the basic principles, whose implementation is then expressed in a wide diversity of applications. Research limitations/implications: Owing to time limitations, the research only included 16 in-depth interviews. In order to enlarge the external validity of this research more interviews should be executed. Originality/value: The framework of this research is unique in term of its topic and analysis processes.
Keywords: 650; t-shape dilemma; integrative approach; knowledge management; learning organization